The Effect of Phosphate Fertilizer and Lime in Ultisol Soil on Phosphate and Protein Leaf Levels of Corn (Zea mays L.) and Soybean (Glycine max L. (Merr)) - Silahooy, Charles (East Asian Journal of Multidisciplinary Research, 2024)
The Effect of Phosphate Fertilizer and Lime in Ultisol Soil on Phosphate and Protein Leaf Levels of Corn (Zea mays L.) and Soybean (Glycine max L. (Merr))